A cross-sectional and longitudinal study on the protective effect of bilingualism against dementia using brain atrophy and cognitive measures - Víctor Costumero; Lidon Marin-Marin; Marco Calabria; Vicente Belloch; Joaquín Escudero; Miguel Baquero; Mireia Hernandez; Juan Ruiz de Miras; Albert Costa; Maria-Antònia Parcet; César Ávila (Alzheimer’s Research & Therapy, 2020)
Abstract Background Evidence from previous studies suggests that bilingualism contributes to cognitive reserve because bilinguals manifest the first symptoms of Alzheimer’s disease (AD) up to 5 years later than monolinguals. Other cross-sectional studies demonstrate that bilinguals show greater amounts of brain atrophy and hypometabolism than monolinguals, despite sharing the same diagnosis and suffering from the same symptoms. However, these studies may be biased by possible pre-existing between-group differences. Methods In this study, we used global parenchymal measures of atrophy and cognitive tests to investigate the protective effect of bilingualism against dementia cross-sectionally and prospectively, using a sample of bilinguals and monolinguals in the same clinical stage and matched on sociodemographic variables. Results Our results suggest that the two groups did not differ in their cognitive status at baseline, but bilinguals had less parenchymal volume than monolinguals, especially in areas related to brain atrophy in dementia. In addition, a longitudinal prospective analysis revealed that monolinguals lost more parenchyma and had more cognitive decline than bilinguals in a mean follow-up period of 7 months. Conclusion These results provide the first prospective evidence that bilingualism may act as a neuroprotective factor against dementia and could be considered a factor in cognitive reserve.